TANTANGAN INTERNATIONAL LABOUR ORGANIZATION (ILO) DALAM UPAYA MENGATASI MASALAH PEKERJA ANAK DI BANGLADESH - Isabella Maria Agave Hutabarat; Idjang Tjarsono (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This Research is a contemporer study which analyzes about the challenge of International Labour Organization (ILO) in action to resolve the child labour problem in Bangladesh. Child labor is a social problem that has become a global issue and the agenda of nations in the world. The term child labor is often defined as work that hampers their childhood, their potential and their dignity, and is harmful to their physical and mental development. Bangladesh is a country with a high rate of child labor with a variety of issues contained therein. ILO as an international organization that deals with welfare has made various efforts but still has some challenges in resolving the problem of child labor in Bangladesh.This study aims to identify and explain the challenges of the ILO in its efforts to eliminate the number of child laborers in Bangladesh. This research was developed based on the framework of pluralism perspective that is supported by the theory of international organization, as well as the level of analysis using the government as the main actor in international relations. The concept leads to qualitative methods and the study of literature as a source of information.The challenges of ILO in its efforts to resolve the problem of child labor in Bangladesh, are the problem of poverty, the culture that assumed the child labour is normal, low education, and law enforcement that is not effective.Keywords: child labour, challenge, International Labour Organization (ILO), Bangladesh